THE EFFECT OF HUMAN DEVELOPMENT INDEX ON ECONOMIC GROWTH IN NORTH LUWU - Raodah Raodah; I Ketut Patra; Muhammad Ikbal (UNIVERSITAS PGRI MADIUN, 2024)
This research aims to determine the influence of the Human Development Index on economic growth in North Luwu Regency. The type of research used is quantitative. The data type is secondary data. This research uses time series data based on the Central Statistics Agency (BPS) of North Luwu Regency. Data collected over the last 13 years using the simple Linear Regression Analysis method. The results of this research show that the Human Development Index (HDI) has a negative and significant effect on Economic Growth. This research shows that the Human Development Index cannot significantly increase the rate of economic growth in North Luwu. The human development index has an influence on economic growth in North Luwu. The author hopes that the government will be more serious in managing human development. In this case, the government must provide assistance to the community, especially in the fields of health and education, so that the community can increase its human resources and government policies are expected to achieve their goals.